Judicial Attitudes and Interpretations toward Interfaith Marriage and Apostasy-Based Divorce: A Study of the Religious and District Courts of Salatiga - Mustofa, Kholifatun Nur (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2025)
Religious difference remains one of the most sensitive and enduring debates in matters of marriage and divorce, often placing judges in complex interpretive positions. This study examines judicial attitudes toward interfaith marriage and divorce on the grounds of apostasy (riddah) in Salatiga, Indonesia. Using a socio-legal approach, this research draws on in-depth interviews with three judges and an analysis of ten judicial decisions issued by the Salatiga Religious Court and District Court. The findings indicate clear divergences in judicial attitudes, largely shaped by differences in educational background, legal reasoning, and normative orientation. Two judges firmly rejected interfaith marriage based on Islamic legal doctrine and concerns regarding family harmony, while another adopted a human rights perspective and did not regard interfaith marriage as inherently problematic. Notably, neither court recorded formal applications for interfaith marriage, as couples often bypassed judicial authorization. In contrast, divorce cases involving apostasy revealed a more flexible judicial stance. Judges implicitly recognized the validity of interfaith marriages conducted in churches, despite the absence of prior approval. For the sake of legal certainty, they reframed religious conversion as continuous marital disputes. This practice reflects judicial efforts to balance textual norms with social realities in pursuit of substantive justice.